Nano‐Ferroelectric for High Efficiency Overall Water Splitting under Ultrasonic Vibration - Su, Ran; Hsain, H. Alex; Wu, Ming; Zhang, Dawei; Hu, Xinghao; Wang, Zhipeng; Wang, Xiaojing; Li, Fa‐tang; Chen, Xuemin; Zhu, Lina; Yang, Yong; Yang, Yaodong; et al. (Angewandte Chemie International Edition, 2019)
Piezocatalysis, converting mechanical vibration into chemical energy, has emerged as a promising candidate for water‐splitting technology. However, the efficiency of the hydrogen production is quite limited. We herein report well‐defined 10 nm BaTiO3 nanoparticles (NPs) characterized by a large electro‐mechanical coefficient which induces a high piezoelectric effect. Atomic‐resolution high angle annular dark field scanning transmission electron microscopy (HAADF‐STEM) and scanning probe microscopy (SPM) suggests that piezoelectric BaTiO3 NPs display a coexistence of multiple phases with low energy barriers and polarization anisotropy which results in a high electro‐mechanical coefficient. Landau free energy modeling also confirms that the greatly reduced polarization anisotropy facilitates polarization rotation. Employing the high piezoelectric properties of BaTiO3 NPs, we demonstrate an overall water‐splitting process with the highest hydrogen production efficiency hitherto reported, with a H2 production rate of 655 μmol g−1 h−1, which could rival excellent photocatalysis system. This study highlights the potential of piezoelectric catalysis for overall water splitting. The oscillatory polarization state of a nano‐ferroelectric with the coexistence of three ferroelectric phases (T+O+R) leads to an imbalanced charge state on the sample surface and creates an alternating cascade of a space charge release and attraction under ultrasonic vibration, thus generating hydrogen and oxygen via direct water decomposition.